2017
DOI: 10.1039/c6qo00615a
|View full text |Cite
|
Sign up to set email alerts
|

A [3 + 2]–[4 + 2]–[3 + 2] cycloaddition sequence of isoquinolinium ylide

Abstract: A unique [3 + 2]–[4 + 2]–[3 + 2] cycloaddition sequence of isoquinolinium ylide is investigated to afford polycyclic compounds with ten stereogenic centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 52 publications
0
8
0
2
Order By: Relevance
“…Initially, the conditions for the reaction of N -cyanomethylisoquinolinium chloride with 2-benzylidene-1,3-indanedione were briefly examined on the basis of our previously established reaction conditions for the N -phenacyl and N -ethoxycarbonylmethylisoquinolinium salts. 8 When the reaction was carried out in the solvent of MeOH, EtOH, CH 3 CN and dry tetrahydrofuran (THF) in the presence of triethylamine as base for about 10 h, the expected spiro[indene-2,1′-pyrrolo[2,1- a ]isoquinoline], 1a , was obtained in 47, 51, 56, and 81% yields. When 1,4-diazabicyclo[2.2.2]octane (DABCO), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), and piperidine were used as base, the reaction in dry THF gave 45, 59, and 57% yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the conditions for the reaction of N -cyanomethylisoquinolinium chloride with 2-benzylidene-1,3-indanedione were briefly examined on the basis of our previously established reaction conditions for the N -phenacyl and N -ethoxycarbonylmethylisoquinolinium salts. 8 When the reaction was carried out in the solvent of MeOH, EtOH, CH 3 CN and dry tetrahydrofuran (THF) in the presence of triethylamine as base for about 10 h, the expected spiro[indene-2,1′-pyrrolo[2,1- a ]isoquinoline], 1a , was obtained in 47, 51, 56, and 81% yields. When 1,4-diazabicyclo[2.2.2]octane (DABCO), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), and piperidine were used as base, the reaction in dry THF gave 45, 59, and 57% yields.…”
Section: Resultsmentioning
confidence: 99%
“…7b The base-mediated three-component reaction of N -alkoxycarbonylmethylisoquinolinium salts, aromatic aldehydes, and 1,3-indanedione afforded the unprecedented complex polycyclic compounds, in which the generated isoquinilonium ylide not only behaved as a reactive 1,3-dipole but also acted as a useful diene to accomplish sequential 1,3-dipolar cycloaddition and the Diels–Alder reaction (eq 3 in Scheme 1). 8 In continuation of our aim to exploit the potential synthetic applications of the heteroaromatic N -ylides, 8 herein, we wish to reveal the unprecedented reactions of N -cyanomethylisoquinolinium chloride with 2-arylidene-1,3-indanediones under different reaction conditions. The reaction not only gave the normal spiro[indene-2,1′-pyrrolo[2,1- a ]isoquinoline] derivatives through the normal 1,3-dipolar cycloaddition reaction but also afforded unique spiro[benzo[ f ]imidazo[5,1,2- cd ]indolizine-4,2′-indene] derivatives by the domino cyclization process (eq 4 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst was also reused five times, without significant reduction of activity (Scheme 63). Yan [179] The same research group [180] reported a unique three-component [3 + 2]-[4 + 2]-[3 + 2] cycloaddition sequence of isoquinolinium ylide (330), a tandem reaction of isoquinolinium methylidene containing alkoxycarbonyl and benzoyl substituents, with aromatic aldehyde (331) and indane-1,3-dione (332) for the synthesis of complex polycyclic compounds. An interesting feature of this approach is that the afforded polycyclic compounds contain ten achiral centers meanwhile only one diastereomer formed with high regio-and diastereoselectivity.…”
Section: Eurjocmentioning
confidence: 99%
“…However, this approach has certain limitations associated with generation of stoichiometric amount of conjugated-acid waste, usually requirement of alkalic reaction conditions and separation of the pyridinium salts after the alkylation step (Scheme 1, path b). [7,8] Thus, the catalytic generation of the pyridinium ylide from the diazo compounds (or other carbene precursors) and pyridine derivatives under mild and neutral conditions is a more appealing method in terms of step-and atom-economy in comparison to the latter. Although review articles on the pyridinium ylide chemistry have been published about 10 years ago, [7] which are mainly focused on the stoichiometric version (Scheme 1 path b).…”
Section: Introductionmentioning
confidence: 99%